Judicial Considerations in Adjudicating Child Maintenance Claims from the Perspective of Progressive Legal Theory nad Maqashid Al-Syariah (A Normative Juridical Study on Decision Number 4115/PDT.G/2023/PA.KAB.MLG. and Decision Number 229/PDT.G/2021/PA SAK - Hamzah, Hamzah; Tanjung, Dhiauddin; Siregar, Ramadhan Syahmedi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research analyzes judges' considerations in adjudicating lawsuits for child māḍiyah maintenance from the perspective of progressive legal theory and Maqashid Al-Syariah, with case studies on Decision Number 4115/Pdt.G/2023/PA.Kab.Mlg. and Decision Number 229/Pdt.G/2021/PA Sak. The study results show that judges strive to achieve substantive justice by prioritizing the child's welfare. Progressive legal theory is applied by considering the social context and factual conditions. At the same time, Maqashid Al-Syariah ensures that decisions are aligned with the objectives of sharia, namely the protection of religion, life, intellect, lineage, and property. The combination of these two perspectives allows judges to make formally and substantively just decisions, and provide optimal protection for children's rights. This study highlights the importance of flexibility and adaptation in the application of law to achieve true justice in cases of child māḍiyah maintenance.